Cinéma Cinéma : Contemporary art and the cinematic experience. - Banner, Fiona; Becker, Julie; Bismuth, Pierre; Bloemheuvel, Marente; Bürgi, Bernhard; Chaloin, Françoise; Debbaut, Jan; Doswald, Christoph; Erkintalo, Tina; Esche, Charles; Ferguson, Russell; Gordon, Douglas; et al. (Rotterdam : NAI Uitgevers, 1999)
Cinéma, Cinéma explores the fascination of a number of visual artists for the phenomenon of cinema. The publication offers a broad range of artistic approaches to the world of film and explains the various ways in which artists use the cinematographic experience to formulate their own ideas. The artists are, for example, interested in the various storytelling opportunities that cinema provides. They investigate the field of tension between fiction and reality, and study the role that cinema plays in the perception and reconstruction of both historical and current events. Attracted by the power of cinema, the artists featured here analyze its components and delve into the specific qualities of the cinematic grammar, of the way in which a film is constructed, a process that includes camera use, montage, lighting, framing, casting, mise en scène and so forth. In so doing they make use of multiple projection screens, sound, ,photography, slide projections and props. Each chapter spotlights one artist, offers an extensive array of visual material and furnishes an accompanying explicative text. In addtion two essays introduce the book. Jaap Guldemond (curator of the Stedelijk Van Abbemuseum Eindhoven) provides a context for, and an explanation of the principles that underlie this publication and the exhibition of the same name. Jean-Christophe Royoux (French critic and authority on the relationship between visual art and cinema) analyzes the different styles of approach that artists take to the so-called cinéma d'exposition.
biog., ind. tent., gr. tent., bibliog. p. 119-127
Engels
Cinéma Cinéma : Contemporary Art and the Cinematic Experience, Van Abbemuseum Eindhoven, 13 February - 24 May 1999
boek
Keywords: Ahtila, Eija-Liisa; Banner, Fiona; Becker, Julie; Bismuth, Pierre; Draeger, Christoph; Girardet, Christoph; Gordon, Douglas; Huyghe, Pierre; Koester, Joachim; Lewis, Mark; Lockhart, Sharon